Lossless image authentication algorithm based on adaptive combinations of image basic blocks - Jian-gao LUO; Guo-qiang HAN; Yan WO; Xiang-yang LI (Tongxin xuebao)
As the existing block-wise lossless image authentication algorithms were inadequate in the division of image authentication blocks,a novel lossless image authentication algorithm based on adaptive combinations of image basic blocks was proposed.The image authentication block was composed of some basic image blocks by the source image characteristics and requirements of watermarking image fidelity,and the authentication code was generated by a digital signature algorithm and embedded into the authentication block via a lossless watermarking algorithm.Moreover,the robust transmission of the image ID was achieved via multi-embedding,and using the ID and authentication block ID the image authentication algorithm could prevent vector quantizationattack.Theoretical analyses and experimental results demonstrate that the algorithm not only improves the existing tamper localization accuracy but also has strong adaptability and can resist vector quantization attack.